Adsorption and Thermal Evolution of the Carbonyl-functionalized Ionic Liquid [5-oxo-C6C1Im][NTf2] on Pt(111): A Combined IRAS, STM, and DFT Study - Bühlmeyer, Hanna; Knörr, Lukas; Steffen, Julien; Eschenbacher, Roman; Hauner, Jonas; Görling, Andreas; Libuda, Jörg (Chemistry - A European Journal, 2024)
The coating of heterogeneous catalysts with ionic liquids enables precise tuning of catalytic activity and selectivity. Recently, the fundamentals of solid catalysts with ionic liquid layers have been extensively studied. So far, investigations have focused on simple ILs without specialized functional groups. In our current work, we aim to involve functionalized ILs to take advantage of the interactions between these functional groups, the catalyst, and the reactants. In this study, we investigated the interaction, and thermal stability of the carbonyl-functionalized IL [5-oxo-C6C1Im][NTf2] on Pt(111) by infrared reflection absorption spectroscopy and scanning tunneling microscopy. In addition, we performed density functional theory calculations to support our interpretation. At 200 K and low coverage, the carbonyl group of the [5-oxo-C6C1Im]+ cation is oriented parallel to the Pt(111) surface. With increasing coverage, the alkyl chain detaches from the surface and orients towards the vacuum. The [NTf2]− anion adsorbs parallel to the surface via the oxygen atoms of the SO2 groups. At higher coverage, at least one of the SO2 groups completely detaches from the surface. Upon heating to 250 K, we observe decomposition and partial desorption of [5-oxo-C6C1Im][NTf2], with further decomposition and desorption occurring between 350 and 400 K.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Infrared reflection absorption spectroscopy; Ionic liquids; Scanning tunneling microscopy; Pt(111); SCILL